Computational investigation on the structure-activity relationship of the biradical mechanism for monoamine oxidase - ERDEM, SAFİYE (SPRINGER WIEN, 2011)
Although a considerable amount of mechanistic data has accumulated in literature, the detailed mechanism for amine oxidation by monoamine oxidase is still controversial. The single electron transfer mechanism (SET) has been widely discussed, but not completely understood yet. In the present study, the modified SET mechanism, proposed by Silverman et al., was explored by quantum chemical calculations. The ONIOM method was applied with UDFT/B3LYP/6-31 + G(d,p) for the higher layer and with UHF/6-31G(d) for the lower layer. Isoalloxazin heterocyclic ring and benzylamine were employed in the calculations to represent flavin and the substrate, respectively. The substituents CH3, OH, OCH3, H, F, Cl, Br, CF3 and NO2 were incorporated at the para position of benzylamine to explore structure-activity relationships. The structures of the reactant complex, transition state and product complex were fully optimized. Activation energies and rate constants of all the reactions were calculated. The results obtained from the linear regression analysis showed that electron-donating groups at the para position of benzylamine increase the reaction rate. A linear but inverse correlation between the log of the calculated rate constants (log k) and the electronic parameter of the substituent was observed (R = 0.93). In accordance with this result, a relatively weak inverse correlation between the calculated log k and the experimental log k was obtained (R = 0.78). The results are contrary to the previous kinetic experiments and the computational study on the effect of p-substituents in the flavin reduction of MAO A by p-substituted benzylamine analogs. Therefore, they present negative evidence for the modeled biradical mechanism.
Keywords: MAO mechanism; Substituent effect; Amine oxidation; Flavoenzyme; Flavin; AMINE-OXIDATION; CATALYTIC-PROPERTIES; BENZYLAMINE ANALOGS; CRYSTAL-STRUCTURES; AROMATIC CAGE; MAO-A; INSIGHTS; ONIOM; RESOLUTION; SITE